Exploring The Impact of E-Banking on The Sustainability of Muslim-Owned Micro Enterprises in Kwara State, Nigeria - Rafiu, Abdullahi Abdul; Jibril, Ayuba Olaniyi; Shehu, Sakariyahu (INJIES: Journal of Islamic Education Studies, 2025)
The study was carried out to exploring the impact of e-banking on the sustainability of Muslim-owned micro enterprises in Kwara state, Nigeria, two research question along with two hypotheses guided the study. The study adopted a descriptive survey research design, comprising 5,575 registered Muslim-owned micro enterprise owners in the state. Morgan’s table sampling techniques was use to select 500 respondents from the entire population of the study. Data collected was done through a self-designed structured questionnaire comprising 20-items, and its relevance and clarity was done by three experts. To ensure its reliability, a pilot study was conducted with 15 registered Muslim-owned micro business owners in Osun State, yielding a reliability coefficient of 0.89. Data collection took place across the three senatorial zones of Kwara State, by the researcher and three research assistants. The collected data were analyzed using Simple Linear Regression (SLR) at a 0.05 significance level for hypothesis testing, while the research question was analyzed using mean and standard deviation. The findings among other indicated that e-banking significantly impact the future of Musilim-owned micro enterprises, particularly in purchasing and selling activities, while also highlighting concerns about online theft, e-banking fraud, and financial management. The study emphasized that while e-banking improves business transactions and enhances financial efficiency, it also exposes businesses to certain risks. Based on these insights, it was recommended that Muslim-owned micro business owners should integrate e-commerce platforms linked to e-banking services to broaden their market reach and improve financial practices. Furthermore, financial institutions are encouraged to enhance their security measures and offer training programs to assist Muslim-owned micro business owners in mitigating the risks associated with e-banking.